Impact of differences in legal risk assessment on compliance norms in multinational corporations (Ius Novum, 2019)
International corporations operating within the multijurisdictional environment are confronted with the daily challenge of staying in compliance with constantly varying legal and regulatory risks. To assure the conformity with the binding norms, they have to introduce complex internal legal and compliance management mechanisms. These mechanisms consist of the risk identification, assessment and mitigation measures. The core of the difficulty results from the cultural differences in the legal and regulatory systems on the diversified territories in which global corporations operate. The commonly used remedy applied by corporations that strive to assure the legal and regulatory uniformity across the geographies are internal compliance norms. However, the universally introduced compliance norms trigger both difficulties in applying them due to the cultural differences and, for the same reasons, problems caused by various interpretations of those norms. The legal workarounds addressed in this article show how corporations deal with the challenge of their multicultural legal and regulatory surroundings.
Keywords: international corporations; compliance; legal and regulatory risks; differences in legal cultures; interpretation rules; supervisory regulations